2012
DOI: 10.1001/archsurg.2012.1148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prior Abdominal Surgery, Obesity, and Lumbar Spine Level on Anterior Retroperitoneal Exposure of the Lumbar Spine

Abstract: To evaluate the effects of prior abdominal surgery and obesity and the level of spine exposure on the technical aspects and complications of anterior retroperitoneal exposure of the lumbar spine (ARES).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…Mogannam et al reviewed 476 patients who underwent anterior retroperitoneal exposure of the lumbar spine and found that more perioperative complications occurred in patients with larger BMI 106. These included higher rates of vascular injury and overall complications, such as bowel and ureteral injuries, postoperative ileus, neurologic deficit, and cardiopulmonary and wound issues.…”
Section: Anatomy and Physiology Of The Intervertebral Diskmentioning
confidence: 99%
See 1 more Smart Citation
“…Mogannam et al reviewed 476 patients who underwent anterior retroperitoneal exposure of the lumbar spine and found that more perioperative complications occurred in patients with larger BMI 106. These included higher rates of vascular injury and overall complications, such as bowel and ureteral injuries, postoperative ileus, neurologic deficit, and cardiopulmonary and wound issues.…”
Section: Anatomy and Physiology Of The Intervertebral Diskmentioning
confidence: 99%
“…Mogannam et al reviewed 476 patients who underwent anterior retroperitoneal exposure of the lumbar spine and found that more perioperative complications occurred in patients with larger BMI. 106 These included higher rates of vascular injury and overall complications, such as bowel and ureteral injuries, postoperative ileus, neurologic deficit, and cardiopulmonary and wound issues. In a cohort of 1,190 patients undergoing treatment for lumbar disk herniation, Rihn et al showed that obese patients (BMI > 30) required significantly longer operation times and had more blood loss and increased length of stay.…”
Section: Anatomy and Physiology Of The Intervertebral Diskmentioning
confidence: 99%
“…Nourian et al noted major venous injuries in 4.6% of cases and major arterial injuries in 1.6% [ 5 ]. When minor injuries are included, the historical rate of vascular injury exceeds 10% [ 6 , 7 , 8 ]. The use of the minimally invasive retractor allows for a lateral exposure to the spinal column, thus avoiding potential hazards of iliac vessels when performing more anterior exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of all-cause complications for anterior exposures has been reported to be between 40 and 50 per cent, 1,3 and, in one study, as high as 82 per cent. 15 Vascular injury is the most commonly reported complication, with published rates from 1 to 15 per cent. [2][3][4][5][6]11 Based on these rates, our 2.1 per cent incidence of major vascular injury is acceptable.…”
Section: Discussionmentioning
confidence: 99%